2009
DOI: 10.4067/s0716-10182009000600008
|View full text |Cite
|
Sign up to set email alerts
|

Infecciones parasitarias intestinales y factores asociados a la infección por coccidias en pacientes adultos de un hospital público de Lima, Perú

Abstract: Objective: To evaluate the frequency of intestinal parasites and risk factors associated with coccidian infection in patients cared for at a public hospital in Lima-Peru. Methods: A descriptive, cross-sectional study was conducted using reports of the parasitology laboratory. Patients included were >18 years, who gave at least one faecal sample for parasitologic evaluation. Logistic regression was used to calculate Odd Ratios (OR) and 95% confidence intervals. Results: 2.056 patients were included in the analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
4
0
1
Order By: Relevance
“…In Africa, prevalence levels varied greatly among countries, ranging from 0.2% to 28% (Henry et al ., 1986; Kelly et al ., 1996; Cranendonk et al ., 2003; Olusegun et al ., 2009; Vouking et al ., 2014; Sangaré et al ., 2015; Casmo et al ., 2018). In South America prevalences ranged from 1.1% to 30.0% (Jarpa Gana, 1966; Sauda et al ., 1993; Certad et al ., 2003; Kaminsky et al ., 2007; Chincha et al ., 2009; Cardoso et al ., 2011; Assis et al ., 2013; Barcelos et al ., 2018). Several studies were performed in Brazil where high variations in prevalence were also reported (1.1–13.0%) (Sauda et al ., 1993; Cardoso et al ., 2011; Assis et al ., 2013, Barcelos et al ., 2018).…”
Section: Distribution and Prevalencementioning
confidence: 99%
See 1 more Smart Citation
“…In Africa, prevalence levels varied greatly among countries, ranging from 0.2% to 28% (Henry et al ., 1986; Kelly et al ., 1996; Cranendonk et al ., 2003; Olusegun et al ., 2009; Vouking et al ., 2014; Sangaré et al ., 2015; Casmo et al ., 2018). In South America prevalences ranged from 1.1% to 30.0% (Jarpa Gana, 1966; Sauda et al ., 1993; Certad et al ., 2003; Kaminsky et al ., 2007; Chincha et al ., 2009; Cardoso et al ., 2011; Assis et al ., 2013; Barcelos et al ., 2018). Several studies were performed in Brazil where high variations in prevalence were also reported (1.1–13.0%) (Sauda et al ., 1993; Cardoso et al ., 2011; Assis et al ., 2013, Barcelos et al ., 2018).…”
Section: Distribution and Prevalencementioning
confidence: 99%
“…Since the 1990s, many studies have been reported on C. belli infection in immunocompromised patients worldwide. The prevalence of infection to C. belli is significantly higher in HIV-infected patients compared to HIV-negative patients in different geographical areas: 0% (0/81) in HIV-negative vs 9.9% (13/131) in HIV-positive individuals in Brazil (Sauda et al ., 1993); 0.4% (1/266) in HIV-negative patients vs 28% (18/65) in HIV-positive patients in India (Kulkarni et al ., 2013); 0% (0/164) in HIV-negative patients vs 12.2% (26/214) in HIV-positive patients in Ethiopia (Assefa et al ., 2009); and 2.9% (50/1722) in HIV-negative patients compared to 8.4% (28/334) in HIV-positive patients in Peru (Chincha et al ., 2009). In HIV-infected persons, C. belli prevalence rates varied from 0.4% to 28% (DeHovitz et al ., 1986; Ros et al ., 1987; Sauda et al ., 1993; Lagrange-Xélot et al ., 2008; Chincha et al ., 2009; Kulkarni et al ., 2013; Swathirajan et al ., 2017; Barcelos et al ., 2018; Casmo et al ., 2018) (Table 2).…”
Section: Distribution and Prevalencementioning
confidence: 99%
“…Intestinal parasitoses (IP) are worldwide common infections, especially in countries with water contamination problems and poor sanitary conditions (7). IP prevalence rates are related to factors that affect the quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…La giardiasis es un importante problema de salud pública en el país debido a la alta prevalencia en humanos, especialmente en niños (Chincha et al, 2009;Alvarado et al, 2011). El estudio pretendió demostrar la presencia de Giardia sp en caninos que acuden a áreas de recreación como parques públi-cos.…”
Section: Discussionunclassified